Compression gloves for patients with hand arthritis (C-GLOVES): A feasibility study - Hammond, Alison; Prior, Yeliz (Hand Therapy, 2021)
Introduction Compression gloves are frequently provided to patients with hand arthritis. Evidence for effectiveness is limited. The aim of this study was to determine feasibility of recruitment, assessment and treatment procedures, in preparation for a future compression glove trial. Methods A non-randomised feasibility study with out-patients with either undifferentiated inflammatory arthritis, rheumatoid arthritis or hand osteoarthritis, with moderate to severe hand pain. All received Isotoner™ compression gloves provided by rheumatology occupational therapists. The main outcomes were feasibility of recruitment, assessment and treatment procedures, trial outcome selection and sample size calculation. Participants were assessed at baseline and four weeks. Assessments included: numeric rating scales (0–10) of hand pain (on activity, at rest, at night) and stiffness; hand joint swelling; finger flexion; and hand function (Grip Ability Test). Results Of 318 patients screened, 86/204 (42%) of inflammatory and 68/114 (60%) of hand osteoarthritis patients were eligible. Of these, 41 (48%: age: 59.10 (SD 12.54) years) and 32 (47%: age: 60.75 (SD 8.64) years) respectively, consented. All completed four-week follow-up. Assessment and treatment protocols were feasible. Hand pain on activity and at night, stiffness, joint swelling, finger flexion and hand function improved: e.g. hand pain on activity: inflammatory arthritis change = −0.95 (SD 2.26; p = 0.01); osteoarthritis −1.57 (SD 1.78; p = 0.001). Participants reported improved hand pain, stiffness and hand function as main benefits. Conclusion Procedures tested were feasible. The most relevant primary outcome was hand pain on activity. Future trials would need 161 participants (Inflammatory arthritis) and 151 (hand osteoarthritis). Trial registration: Clinical Trials.Gov: NCT01874067